Developing the traditional knowledge of the Orang Asli community in Malaysia / Intan Nurulhani Baharuddin, Norshakila Yusof and Dr. Lim Hin Fui - Baharuddin, Intan Nurulhani; Yusof, Norshakila; Lim, Hin Fui (Unit for Research and Intellect Application (UfoRIA), 2009)
It is generally recognised the estimated 190,000 Orang Asli in Peninsular Malaysia have traditional knowledge that could be further utilised for the development of bio-technology products. In the meantime, it is observed that such knowledge is dwindling and could possibly be lost in the wave of modernisation. It is essential to record and develop such knowledge for local and national interests. It is within this context that under the Ninth Malaysia Plan (2006-2010), the Ministry of Natural Resources and Environment (NRE) has made a special effort to document Traditional Knowledge (TK). This project is implemented by Forest Research Institute Malaysia (FRIM) and the main objective is to establish a database on traditional knowledge of medicinal and aromatic plants used by Orang Asli in Peninsular Malaysia. This paper concerns the partnership and involvement between researchers and Orang Asli community in documenting the traditional knowledge as well as capacity building. The whole process involves initial discussion with community leaders. This was followed by two awareness workshops held at RPS Iskandar, Bera, Pahang and at the RPS Banun, Gerik, Perak. Two socio-economic surveys were subsequently conducted in these two locations. The information gathered is being analysed and is expected to provide input to policy makers in terms of conserving and developing the traditional knowledge of the Orang Asli communities. Challenges in carrying out the project are also highlighted in this paper.